EFFECT OF FeCl3 COAGULAN DOSAGE ON DECREASING TURBIDITY OF LEATHER TANNERY WASTE PROCESSING - Nanda Brilian Tantri; Swatika Juhana; Ragil Yuliatmo (Politeknik ATK Yogyakarta, 2023)
The leather tanning industry is one of the industries that produces liquid waste. The liquid waste of the leather tanning industry contains pollutants with a high level of turbidity. This research was conducted to determine variations in the dose of FeCl3 as a coagulant to reduce the turbidity of leather tanning wastewater. The coagulant added was 5 mL of FeCl3 with various doses of 1%, 2%, 3%, 4% and 5%. The optimum dose of FeCl3 coagulant to treat 300 mL of liquid waste is 3% with a volume of 5 mL, which means that 500 mg/L or 500 ppm is needed. The results showed a decrease in turbidity at the optimum dose was 94%, a decrease in chromium content of 83,53%. This shows that the effect of FeCl3 on reducing total chromium content and turbidity gives quite good results.